Socioeconomic activities that use natural resources from the coastal and marine areas of Costa Rica and their relationship with climate variability - Moreno Díaz, Mary Luz (2017)
Climate variability could have negative effects on the productivity of coastal zone activities. Because of the above and because Costa Rica is a country in which coastal activities, related to natural resources, have great social and economic relevance, in the present article an analysis is made to verify if these effects are presented and to provide tools for making Decisions in these areas. For the above, a characterization of the fishing and the tourist sector for the period 1990-2005 is made. The amount of artisanal and industrial fishing is related, the number of tourists, hotels and rooms in coastal areas with some climatic variables in order to identify the main interactions between them. The climatic variables used were Sea Surface Temperature (SST) and Precipitation (P). Pearson correlation coefficients were used between productive and climatic variables. When correlating the different climatic variables with the amount of fishing it was found that when the coefficient was statistically significant, the climatic variable in all cases has negative correlations with the catches, that is to say when it increases for example the SST of the Sea decreases the amount of fishing. In the case of tourism, the coefficients were not statistically significant in the annual variables but in the quarterly ones. The methodology applied in this article can be used to make inferences about the behavior of productive variables for specific periods (quarter for example) in the face of climatic variations and to take measures to mitigate the impact.